Systemic Capillary Leak Syndrome as an Initial Presentation of ALK-Negative Anaplastic Large Cell Lymphoma - Laura S. Lourdes; Samer Z. Al-Quran; Nam H. Dang; Merry-Jennifer Markham (Case Reports in Hematology)
Systemic capillary leak syndrome (SCLS) is a rare disease characterized by third spacing of plasma into the extravascular compartment, leading to anasarca, hemoconcentration, and hypovolemic shock. It has been rarely associated with lymphomas, and reports usually indicate that it occurs after antineoplastic treatment. We present the case of a patient with ALK-negative anaplastic large cell lymphoma who presented with SCLS as the initial manifestation of her lymphoma. The SCLS resolved with treatment of the malignancy with steroids and chemotherapy.